2022
DOI: 10.1177/15589447221124270
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Five-Item Frailty Index to Predict Hand and Wrist Surgical Repair Postoperative Outcomes: An ACS-NSQIP Analysis of 11 369 Patients

Abstract: Background: Hand and wrist injuries can cause painful, everyday obstacles for patients. Carefully indexing preoperative patient health conditions may better inform surgical care, leading to improved postoperative outcomes. The purpose of the present study is to evaluate if the Modified-Five Item Frailty Index (mFI-5) can accurately predict postoperative complications for hand and wrist surgical repair. Methods: A retrospective review of the American College of Surgeons’ National Surgical Quality Improvement Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[11][12][13] Ibelli et al conducted a large database study of 11,369 patients and found that a high frailty score was associated with readmission and surgical site infection following hand and wrist surgeries. 26 While those studies did not specifically examine the effect of frailty on patients undergoing TWA, our results show that frail patients undergoing TWA are at increased risk for extended LOS and postoperative complications. It is important to note some of the patients with extended LOS in our study were likely admitted for reasons unrelated to TWA.…”
Section: Discussionmentioning
confidence: 50%
“…[11][12][13] Ibelli et al conducted a large database study of 11,369 patients and found that a high frailty score was associated with readmission and surgical site infection following hand and wrist surgeries. 26 While those studies did not specifically examine the effect of frailty on patients undergoing TWA, our results show that frail patients undergoing TWA are at increased risk for extended LOS and postoperative complications. It is important to note some of the patients with extended LOS in our study were likely admitted for reasons unrelated to TWA.…”
Section: Discussionmentioning
confidence: 50%